Structural Health Monitoring of a Cable-Stayed Bridge Using Regularly Conducted Diagnostic Load Tests - Al-Khateeb, Hadi T.; Shenton, Harry W.; Chajes, Michael J.; Aloupis, Christos (Frontiers in Built Environment, 2019)
The management and maintenance of cable-stayed bridges represents a major investment of human and financial capital. One possible approach to reducing the cost while simultaneously improving the process is by utilizing structural health monitoring (SHM) systems to enable diagnostic load tests to be regularly and efficiently conducted. The Indian River Inlet Bridge (IRIB), a 533-meter long cable stayed bridge, was opened for traffic in 2012. From the very early stages of the design process, the Center for Innovative Bridge Engineering (CIBrE) at the University of Delaware (UD) worked with the Delaware Department of Transportation (DelDOT) and their design-build team of Skanska and AECOM to plan and install a comprehensive structural health monitoring (SHM) system. The SHM system is a fiber-optic based design with more than 120 sensors of varying type distributed throughout the bridge. The system, which not only collects data continuously during normal operation, has also been utilized during regularly scheduled controlled diagnostic load tests being used to monitor ongoing bridge performance. This paper will present results from a series of six diagnostic load tests which have been performed over the first six years of the bridge’s service life (just prior to the bridge’s opening, and then again at six months, one year, two years, four years, and six years). The results of these six load tests have enabled the bridge’s baseline performance to be established. They have also provided an opportunity to develop a process for comparing future biennial tests to the evolving database of results, thereby enhancing DelDOT’s ability to operate and maintain the bridge.